THE COMPARISON OF BUSINESS MODELS AMONG ELDERLY DAY CARE CENTRES IN TAIWAN - Yang, Tai-Ho; Pan, Hsia; Lu, Te-Tsai (Graduate Program of Universitas Tarumanagara, 2023)
Taiwan was enter the super-aged society, therefore, the demand of long-term care (LTC) system for elderly day care (EDC) centre is increasing. The government had also announced that it will promote the construction of more EDC centres. However, the establishment and operation of an EDC centre not only involves regulations, funds, medical care, psychology, etc., but also requires the use of business operation and management knowledge, otherwise it will not be easy to operate normally for a long time and provide better care services for the community. The present study adopts qualitative method which conducts in-depth interviews with five different types of EDC centres executors, there are owned by hospital, societies legal person, consortium legal person, company, personal. According to the competitiveness tool SWOT analysis, the Porter five forces model and the business model canvas, the data collected during the interviews were analysed to understand the business models, advantages, disadvantages, opportunities, and threats of different ownership types of EDC centres, as well as industrial competitiveness. Finally, this research provides reference and advice for new operators who are currently operating or are about to enter the EDC centre industry.